Passive Autocatalytic Recombiner Perfomance Assessment Using COCOSYS (Brazilian Journal of Radiation Sciences (BJRS), 2022)
The progression of a severe accident in nuclear reactors is composed by a diversity of phenomena that areBeyond Design Basis, such as Direct Containment Heating (DCH), Molten Corium Concrete Interaction(MCCI), hydrogen detonation, and others. Currently, there are several devices and systems that allowmitigating the progression of this events, avoiding the failure of the physical barriers between the nuclearpower plant and the environmental. In this context, the present work aims to reproduce the HR-14experiment carried out at the Thermal-hydraulic, Hydrogen, Aerosols and Iodine (THAI) test facility throughthe Passive Autocatalytic Recombiners (PAR) performance assessment with the COCOSYS code. The analysisof the convergence of the results was performed using the Fast Fourier Transform Based Method (FFTBM)and showed that the results had sufficient accuracy with the experimental data.